Nigeria : Request for Purchase under the Rapid Financing Instrument -Press Release; Staff Report; and Statement by the Executive Director for Nigeria. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper presents Nigeria's Request for Purchase Under the Rapid Financing Instrument (RFI). The authorities' immediate actions to respond to the crisis are welcome. The short-term focus on fiscal accommodation would allow for higher health spending and help alleviate the impact of the crisis on households and businesses. Steps taken toward a more unified and flexible exchange rate are also important and unification of the exchange rate should be expedited. Once the coronavirus disease 2019 crisis passes, the focus should remain on medium-term macroeconomic stability, with revenue-based fiscal consolidation essential to keep Nigeria's debt sustainable and create fiscal space for priority spending. Implementation of the reform priorities under the Economic Recovery and Growth Plan, particularly on power and governance, remains crucial to boost growth over the medium term. The emergency financing under the RFI will provide much needed liquidity support to respond to the urgent balance of payments needs. Additional assistance from development partners will be required to support the government's efforts and close the large financing gap.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet